Host CD3+ T-cells can significantly modulate phage treatment effects on bacterial bioburden in mouse models - Li, Renhua; Rouse, Michael; Pace, Brendon T.; Grey, Scott F.; Mclaughlin, Kimberly; Schobel, Seth A.; Simons, Mark P. (Frontiers in Microbiology, 2023)
Wound healing is a complex system including such key players as host, microbe, and treatments. However, little is known about their dynamic interactions. Here we explored the interplay between: 1) bacterial bioburden and host immune responses, 2) bacterial bioburden and wound size, and 3) treatments and wound size, using murine models and various treatment modalities: Phosphate buffer saline (PBS or vehicle, negative control), doxycycline, and two doses of A. baumannii phage mixtures. We uncovered that the interplay between bacterial bioburden and host immune system may be bidirectional, and that there is an interaction between host CD3